2021
DOI: 10.1007/s10103-021-03287-0
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of laser acupuncture tele-therapy for rheumatoid arthritis elderly patients

Abstract: Rheumatoid arthritis (RA) is a progressive common autoimmune disorder and is one of the most functional limiting diseases in elderly. Until recently, its treatment is mainly based on physical locations and meetings while being face to face. However, laser acupuncture tele-therapy approaches can significantly provide the patient with safety during the COVID-19 pandemic as well as changing the disorder’s prognosis. Sixty patients were assigned randomly into 2 groups with 1:1 ratio. Patients in group A are treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The results of the risk of bias assessment of the eight studies are illustrated in Figure 2 . Three trials simply mentioned randomization methods used in their research and omitted details concerning random sequence generation methods [ 11 , 12 , 17 ]. Only three trials indicated what allocation concealment methods were used to maintain privacy after random allocation [ 7 , 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the risk of bias assessment of the eight studies are illustrated in Figure 2 . Three trials simply mentioned randomization methods used in their research and omitted details concerning random sequence generation methods [ 11 , 12 , 17 ]. Only three trials indicated what allocation concealment methods were used to maintain privacy after random allocation [ 7 , 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three trials reported the quality of life of the patients with RA measured by RAQoL [ 7 , 11 , 12 ]. The results of meta-analysis indicated that laser acupuncture had significantly better effects in ameliorating the quality of life, while compared to the control group (MD = −2.32, 95% CI: −4.40 to −0.25, P =0.028) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Used as a means of laser directed treatments for arthritis, significant benefits have been realized by elderly rheumatoid arthritis cases. 9 In this review, a wide ranging search was undertaken to examine AI/ML-based usage or its potential in rehabilitation spheres, rather than diagnostic, measurement, disease classification, or predictive spheres based upon patient and generic data. Its use in surgical or drug based interventions was not examined.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a part that discusses the influence of the telemanagement system on health care development, the aim of this study was to compare two nonpharmacological respiratory treatment methods for home-isolated patients with COVID-19 by using a newly developed telemanagement health care system. The influence of the telemanagement system on health care development has been further discussed in many other articles [ 3 - 6 ], and its discussion was therefore considered outside of the scope of our paper.…”
mentioning
confidence: 99%